Improving Employee Performance Through Physical Work Environment, Emotional Intelligence and Self Leadership - Resa Adhika, I Nyoman; Aristana, I Nengah; Rihayana, I Gede; Putra Salain, Putu Pradiva (Akademi Komunitas MAPINDO, 2023)
Human resources are assets owned by an organization. Without human resources in an entity, operational activities will not be able to run. Entities must be able to empower human resources so that they can produce qualified employee performance. Employee performance is influenced by many factors including the physical work environment, emotional intelligence and self-leadership. This study aims to determine the effect of the physical work environment, emotional intelligence and self-leadership on employee performance. The location of this research is at The Vira Boutique Hotel and Suites Bali. The population uses The Vira Boutique Hotel and Suites Bali employees and a sample of 55 employees. Data analysis technique using Multiple Linear Regression Analysis. From the results of the study, it was found that the physical work environment had a significant positive effect on employee performance, emotional intelligence had a significant positive effect on employee performance, and self-leadership had a significant positive effect on employee performance. Suggestions that can be given by researchers are The Vira Boutique Hotel and Suites Bali should organize the work space properly, provide training to employees and guide employees, and always supervise employees at work. Keywords: Physical Work Environment, Emotional Intelligence, Self Leadership, Employee Performance